2014
DOI: 10.1038/nature13076
|View full text |Cite
|
Sign up to set email alerts
|

Mid-latitude interhemispheric hydrologic seesaw over the past 550,000 years

Abstract: An interhemispheric hydrologic seesaw--in which latitudinal migrations of the Intertropical Convergence Zone (ITCZ) produce simultaneous wetting (increased precipitation) in one hemisphere and drying in the other--has been discovered in some tropical and subtropical regions. For instance, Chinese and Brazilian subtropical speleothem (cave formations such as stalactites and stalagmites) records show opposite trends in time series of oxygen isotopes (a proxy for precipitation variability) at millennial to orbita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…As part of the upward limb of the Hadley Cells, the ITCZ plays a crucial role in global energy redistribution. Temperature-driven meridional displacement of the tropical Hadley Cells and the ITCZ45 induced synchronous shifts in higher latitude climate patterns1 on millennial timescales. High signal-to-noise ratios of millennial-scale climate shifts during glacial periods, largely due to different boundary conditions related to the presence of extensive continental ice sheets, facilitate their detection in proxy records.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As part of the upward limb of the Hadley Cells, the ITCZ plays a crucial role in global energy redistribution. Temperature-driven meridional displacement of the tropical Hadley Cells and the ITCZ45 induced synchronous shifts in higher latitude climate patterns1 on millennial timescales. High signal-to-noise ratios of millennial-scale climate shifts during glacial periods, largely due to different boundary conditions related to the presence of extensive continental ice sheets, facilitate their detection in proxy records.…”
mentioning
confidence: 99%
“…Hemispheric antiphasing of large-scale precipitation patterns in low- and mid-latitude regions, driven by the seasonal migration of the Intertropical Convergence Zone (ITCZ), has been described over orbital timescales, Dansgaard-Oeschger (DO), and Heinrich events123. As part of the upward limb of the Hadley Cells, the ITCZ plays a crucial role in global energy redistribution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1d-f and 2c-e). This area of very high sea surface temperature (SST), persistent strong convection and rainfall, and more depleted vapor extends over the inner tropics and is surrounded by a zone of descending air, less rainfall (Oort and Yienger, 1996;Jo et al, 2014), and more enriched vapor. We consider this pattern as a manifestation of the isotopic amount effect since the isotopic pattern anti-correlates with regional rainfall (Brown et al, 2008;Dansgaard, 1964;Kurita et al, 2011;Lee and Fung , 2007;Lee et al, 2011;Risi et al, 2008;Worden et al, 2007).…”
Section: Spatial Isotope Distributionmentioning
confidence: 99%
“…Carbon isotope compositions of speleothems are also known to be controlled by type of vegetation, biological activities, surface environment, and use and karstification (McDermott, 2004;Cosford et al, 2009). Recent studies showed that carbon isotope compositions of stalagmites also indicate East Asian summer monsoon intensity variations (Jo et al, 2010b(Jo et al, , 2014.…”
Section: Introductionmentioning
confidence: 98%